Restoration of pseudo alpine grasslands in Oiti National Park, Central Greece - Mantzanas K.; Evangelou Ch.; Papanastasis V.P.; Solomou A.; Lyrintzis G.; Ispikoudis S.; Xanthopoulos G.; Tsagari K.; Karetsos G. (Pastoralism and sustainable development: proceedings, 2021)
Pseudoalpine grasslands of Oiti National Park are degraded due to the interruption of the traditional land use practices including transhumance, periodical burning and firewood collection resulting in the dominance of competitive plants and, especially, the invasion of the dwarf juniper (Juniperus communis ssp. nana). The objective of this research was to study the treatments applied imitating traditional management practices for the restoration of grassland flora. In the autumn of 2013, prescribed burning was applied and after one year an area covered with “wolf” grasses was cut. In addition, an area outside the core of the park that was grazed by sheep was divided into three grazing intensity treatments. In all areas, 33 pairs of protected with mesh wire and freely grazed plots were established in spring of 2015. At the end of the growing period, in July, cover and species composition was ocularly estimated, while biomass was measured in quadrats (2015 and 2016). Except the burning treatment, cutting and grazing did not affect plant cover while species composition was positively influenced especially by burning and cutting that favored low growing species with higher nutritional value (Festuca alpina and F. polita). In contrast, biomass was significantly affected only by burning and grazing. It is concluded that moderate sheep grazing should be legally allowed in the core of the Park including the use of prescribed burning which is very effective in controlling dwarf juniper.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)